27 Determinants of referral to developmental resources among neonatal follow-up patients discharged from tertiary neonatal unit from 2005 UNTIL 2014. (19th August 2020) - Saleem, Maad; Hayawi, Lamia; Barrowman, Nick; BenFadel, Nadya; Feberova, Jana; Daboval, Thierry
Abstract: Background: Lower gestational age or birth weight and higher rate of neurodevelopmental impairment have been commonly linked to higher need for developmental resources in premature infants. Existing evidence on need for developmental support in premature infants is limited in description of the needs, timing and method of assessment. Objectives: To identify predictors for the needs for developmental resources among high-risk groups of infants born less than 29 weeks or with a birth weight (BW) less than 1250 grams. Secondarily, to compare the need of referrals to developmental resources and the rate of neurodevelopmental impairment defined as cerebral palsy, global developmental delay, blindness and deafness for this high risk population. Design/Methods: We conducted a retrospective chart review of premature infants < 29+0 weeks GA or BW < 1250 grams born between January 2005 and December 31st 2014, who had at least one visit at the neonatal follow up clinic. Univariate and multivariate logistic regression analyses were conducted to examine potential predictors for referral to developmental resources. Results: The study included 687 infants. Within this high risk population, 579 (85.0%) of infants were referred, of these 153 (26.4%) had one referral, 132 (22.8%) had 2 and 294 (50.8%) had 3 or more referral/s to developmental resources. Most frequent referrals were for speech therapy (339, 50.0%) physiotherapy (319, 46.8%) occupational therapy (262, 38.3%) and infant development program (232, 34.1%). The rates of referral to developmental resources decrease with increasing gestational age. Multivariate logistic regressions showed that gestational age (OR: 1.19, 95% CI: 1.05 - 1.35), birth weight (OR: 0.87, 95% CI: 0.77 - 0.99), female gender (OR: 0.70, 95% CI: 0.49 - 0.99), intraventricular hemorrhage grades III-IV (OR: 3.02, 95% CI: 1.28 - 7.16), and days on mechanical ventilator (OR:1.03, 95% CI: 1.01 - 1.05) were predictors for 2 or more referrals to developmental resources. Cerebral palsy was present in 4.4 % of the study population, deafness in 4% and blindness in 0.6%. The rate of referral to developmental resources was 54 (98.2%) among infants with neurodevelopmental impairment (NDI) compared to 522 (83.9%) in infants without NDI (p value= 0.01). Conclusion: There is substantial need for developmental support among high-risk premature infants. Infants without neurodevelopmental impairments still need significant developmental resources to achieve their outcome.